Rome and the institutions: the State, the Church, the Municipality (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
Rome, what city is it? What subjectivity does it have? Is there a subjectivity in Rome? Turning to the cities of the world we understand that the urban dimension is given by a social subjectivity: Milan was the society of the Brambillas and small entrepreneurs, then it grew, and now it is no longer, in some ways. Turin was the city of Fiat. What was Rome? What subjectivity does it express? Does it express a social subjectivity that becomes an institution or expresses an institution that wants to grow a city? My idea is that Rome is a city that has no subjectivity of its own, it is a city that lives on an institutional identity, lives on institutions and would not live if these were not there.